Evaluation of artemether-lumefantrine efficacy in the treatment of uncomplicated malaria and its association with pfmdr1, pfatpase6 and K13-propeller polymorphisms in Luanda, Angola - Kiaco, Kinanga (2018)
Background: Drug resistance in Plasmodium falciparum has posed an obstacle to effective treatment and challenges many malaria control programmes in endemic areas. In Angola, until 2003, chloroquine (CQ) was used as first-line therapy for uncomplicated malaria. It was replaced initially by amodiaquine and, in 2006, by artemisinin-based combination therapy (ACT) with artemether-lumefantrine (AL, Coartem®). Efficacy study of ACT, conducted in Angola between 2004 and 2005, showed a baseline efficacy of ≈99 %. Methods: 103 malaria patients were enrolled according to WHO proceedings. Patients were followed up with clinical and parasitological evaluations for 28 days, parasite density and identification was evaluated by microscopy, the pfmsp2 were genotyped by nested-PCR, to distinguish parasite recrudescence from new infections; the polymorphisms at codons 86 and 1246 of pfmdr1 gene, and 769 of pfatp6 gene were assessed by PCR-RFLP and sequencing for pfk13-propeller genotype. Results: The cure rate was 91.3 %. The obtained results showed that from 103 patients, 12.6 % (n = 13) still had parasitaemia 1 day after the treatment was finished. On day 0, of the 94 evaluated samples, wild-type alleles were identified in 73.4 % (n = 69) for pfmdr1 N86Y position and only one sample carried the mutant allele (Y) for pfmdr1 1246; 14 % of these samples showed increased pfmdr1 copy number; 100 % (n = 21) had wild-type allele of k13 gene in all the studied positions. Discussion: These results showed changes in parasite profile susceptibility to AL in comparison to the baseline data from 2002 to 2004 and on the genotyping characteristics; the clinical outcome after treatment with AL did not link a particular genotype with treatment failure; observed changes do not provide sufficient evidence for a treatment policy change, but they suggest that a carefully monitoring is needed in this area.